Strategies of Islamic Religious Education in Shaping the Religious Character of Students at Pondok Pesantren Ruqoba Al-Atsary - Anam, Syaiful; Sofia Mendez (Yayasan Azhar Amanaa Yogyakarta, 2025)
Islamic religious education in pesantren plays a crucial role in shaping the religious character of students. This study aims to analyze the strategies of Islamic religious education implemented at Pondok Pesantren Ruqoba Al-Atsary in fostering students’ religious character. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that the applied strategies include classical Islamic text (kitab kuning) learning, reinforcement of Qur’an memorization (tahfidzul Qur’an), habituation of daily worship, role modeling by kyai and teachers, as well as disciplinary supervision. These strategies effectively nurture religious values such as faith, obedience in worship, noble character, and social responsibility among students. Furthermore, the study highlights the relevance of these strategies in addressing contemporary challenges posed by globalization and digital culture, which often undermine the moral foundations of youth. The results also contribute to the theoretical discourse on Islamic education by emphasizing the integration of knowledge, practice, and values. Practically, they provide a model for pesantren and other Islamic educational institutions to strengthen religious character formation. Thus, Islamic religious education strategies at Pondok Pesantren Ruqoba Al-Atsary serve not only to preserve tradition but also to respond adaptively to modern challenges in building a pious and responsible Muslim generation.